2010 IEEE/RSJ International Conference on Intelligent Robots and Systems 2010
DOI: 10.1109/iros.2010.5649668
|View full text |Cite
|
Sign up to set email alerts
|

Design of a personalized r-learning system for children

Abstract: This paper introduces the r-learning (robot -learning) system that utilizes robotic interactions to personalize instructions for individual children. A child who is not familiar with using an educational tool to study could learn readily from educational contents through various interactions with a robot which is based on the behavior control. The contents which are chosen according to a child's learning data extracted by analysis from human-robot interaction data could lift the educational effectiveness. An r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Strifeshadow Fantasy OS was used for a multi-player online game (Chan and Chang, 2004). Designing of UAV helicopter also required special purpose OS (Cai et al, 2005) along with a personalized R-Learning system which operated on Robot Software Platform (Ko et al, 2010). Another multiplayer computer game named Amaze used V-System, Distributed OS (Berglund and Cheriton, 1985).…”
Section: Methodology Categorizing Osmentioning
confidence: 99%
“…Strifeshadow Fantasy OS was used for a multi-player online game (Chan and Chang, 2004). Designing of UAV helicopter also required special purpose OS (Cai et al, 2005) along with a personalized R-Learning system which operated on Robot Software Platform (Ko et al, 2010). Another multiplayer computer game named Amaze used V-System, Distributed OS (Berglund and Cheriton, 1985).…”
Section: Methodology Categorizing Osmentioning
confidence: 99%
“…The ability to create an enjoyable and fun educational context can also be linked to these values. However, concerns are reported in [26][27][28] that children sometimes fear robot tutors because of their appearance or sudden movements. Furthermore, the robot could lead to feelings of anxiety when children become too emotionally attached.…”
Section: Values Attributed To the Introduction Of Robot Tutorsmentioning
confidence: 99%
“…The distance between the child and the robot also seems to affect how the robot tutor is perceived. Some children who actively interacted with a the robot tutor, are reported to be frightened when a robot comes (too) close (Ko et al, 2010). Other studies indicated that the distance between the child and robot could affect female participants more than male participants (Mutlu et al, 2006).…”
mentioning
confidence: 99%